Cattle on the rocks: Understanding cattle mobility, diet, and seasonality in the Iberian Peninsula. The Middle Neolithic site of Cova de les Pixarelles (Tavertet, Osona). - Roger Alcàntara Fors; Richard Madgwick; Laura C Viñas-Caron; Alexandra J Nederbragt; Maria Saña Seguí (PLoS ONE)
Reconstructing past herd mobility, reproduction, and diet is crucial for understanding animal management practices among the first sedentary farming communities. It can also shed light on how domestic animals were integrated into the existing exchange networks of goods, products, and raw materials, and how they contributed to broader economic and social changes during the Neolithic. Despite the longstanding importance of cattle (Bos taurus) to herders, the role of cattle in the daily, seasonal, and annual cycle of activities of early farming communities remains relatively poorly understood. This study focuses on the Middle Neolithic site of Cova de les Pixarelles (3942-3632 cal. BCE) one of the few sites in the Iberian Peninsula from this period with a substantial collection of faunal remains. The site is particularly notable for its high proportion of cattle remains. Previous research on the cattle bone assemblage from Cova de les Pixarelles has included comprehensive archaeozoological, palaeopathological, and biomechanical analyses-an innovative, integrative approach in Mediterranean archaeology that offers an exceptional level of biographical detail. This study uses bulk bone collagen carbon (δ13Ccoll) and nitrogen (δ15N) isotopes, and sequential analysis of enamel bioapatite oxygen (δ18O) and carbon (δ13Ccarb) isotopes to further enhance our understanding of animal management practices during the Middle Neolithic, providing new insights on the diet, mobility and reproduction patterns of cattle. Results indicate that the Neolithic communities that used Cova de les Pixarelles managed these animals to obtain optimal pastures, moving them seasonally from lowland areas to higher mountain plateaus and carefully managing their reproduction cycles. We suggest a nuanced herding approach, combining open-range grazing with an ecological division of herds based on age, sex, and reproductive function, and seasonal vertical mobility, contributing to a complex but efficient herding system during the Middle Neolithic.